Pengembangan Media Pembelajaran Interactive Picture Berbasis Canva Pendidikan Pancasila untuk Meningkatkan Hasil Belajar Kelas V - Arif Fajar, Uli; Aeni, Kurotul (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This research aims to develop a design, test the feasibility, and test the effectiveness of Canva-based Interactive Picture learning media. effectiveness of Canva-based Interactive Picture learning media material on the diversity of my Indonesian culture in class V SDN 02 Sekaran. This research method with the Borg and Gall development model. Borg and Gall development model. The subjects in this study were fifth grade students of SDN 02 Sekaran. The data collection techniques applied included observation, interviews, documentation, questionnaires, and tests. Product quality was evaluated by media, material, and teacher and student validators. Product effectiveness was analyzed using preliminary data analysis techniques through normality test and homogeneity test, as well as final data analysis through paired t-test and N-gain test. Research results showed that the Canva-based Interactive Picture media design material diversity of Indonesian culture in my Canva-based Interactive Picture class. class was successfully developed. The results of the large group T-test calculation amounted to 8.6059 where t table 1.6972 is said to be effective, it can be concluded that H1 is rejected and H2 is accepted. and H2 is accepted. N-Gain in the large group trial obtained a score of 0.6494 with moderate criteria. with moderate criteria. The conclusion in this study is that the learning media Canva-based Interactive Picture learning media on cultural diversity Indonesiaku class V SDN 02 Sekaran was successfully developed, feasible to use as a learning media and effective to improve student learning outcomes. as a learning media and effective for improving student learning outcomes at SDN 02 Sekaran.